Mesin Chopper untuk Meningkatkan Kualitas dan Kuantitas Pakan Usaha Ternak Kambing “Arrahman” - Rany Puspita Dewi; Trisma Jaya Saputra; Tri Puji Rahayu (Warta LPM, 2024)
The "Arrahman" partner is located in Kerten, Krincing Village, Secang District, Magelang manages around 200 to 300 goats. The process of preparing cattle fodder such as elephant grass and corn stalks is done manually using a knife. It causes the feed preparation process take longer considering the large number of goats being managed. The aim of this activity is to contrive and manufacture a chopper to help the process of cutting grass feed more effectively and efficiently. Because it is able to produce more feed capacity in a shorter time with a finer size. Activities are carried out in several stages. The first step is data accumulation and coordination together with partner. Continuing to the next step, the development of solving partner problems through chopper design. The method for measuring the efficiency and effectiveness of cutting cattle fodder is done by quantifying the capacity and quality of cattle fodder produced and quantifying the amount of rising in insight and knowledge of residents which is carried out by looking at before and after the application of the chopper. The primary result is a chopper with a capacity of 100 kg/hour with a 5.5 hp gasoline engine. Chopper parts can be disassembled and assembled, making it easier for partners to maintain and repair. The chopper increases the capacity of cutting animal feed to 100 kg/hour. The activity is able to increase residents' understanding and insight by up to 90%. It is because through design and construction activities, residents are able to understand and gain new insight into the process of making chopper machines.